Business cycle synchronisation: disentangling trade and financial linkages - Stéphane Dées; Nico Zorell (European Central Bank (ECB), 2011)
Drawing on a large sample of countries, this paper explores whether closer economic ties between countries foster business cycle synchronisation and disentangles the role of the various channels, including trade and financial linkages as well as the similarity in sectoral specialisation. Overall, our results confirm that trade integration fosters business cycle synchronisation. Similar patterns of sectoral specialisation also lead to closer business cycle co-movement. By contrast, it remains difficult to find a direct relationship between bilateral financial linkages and output correlation. However, our results suggest that financial integration affects business cycle synchronisation indirectly by raising the similarity in sectoral specialisation. Through this indirect link, financial integration tends to raise business cycle comovement between countries.
Keywords: E32; F41; E44; 330; financial integration; international business cycle; international transmission of shocks